Ekspor dan daya saing cassiavera Indonesia – China di Pasar Internasional - Nurhayani, Nurhayani; Artis, Dearmi; Parmadi, Parmadi (Jurnal Paradigma Ekonomika, 2021)
The plantation sector is a major sector that has an important role in Indonesia both in terms of increasing income and in balancing environmental preservation and as an instrument of equitable development of the people. One of the commodities in the plantation sector is Cassiavera. This study aims to determine and analyze the effect of area, production, exchange rate and economic growth on the export volume of Cassiavera. This study uses secondary data and uses the ECM and RCA analysis tools. In the long run, all variables, either simultaneously or partially, affect the Cassiavera export variable. Whereas in the short term partially or individually, only the economic growth variable affects Cassiavera exports and simultaneously or together all variables affect Cassiavera exports. Indonesian Cassiavera has greater competitiveness than China, which is shown by Indonesia’s higher RCA value than China. Â